Overexpression of SlRBZ Results in Chlorosis and Dwarfism through Impairing Chlorophyll, Carotenoid, and Gibberellin Biosynthesis in Tomato - Fan, Mingqin; Gao, Shenghua; Ren, Junling; Yang, Qihong; Li, Hanxia; Yang, Changxian; Ye, Zhibiao (Frontiers in Plant Science, 2016)
ZFPs play important roles in many biological processes, including plant development, stress response, and phytohormone response. RanBP2-type zinc finger transcription factors have been characterized in animals and humans. However, their functions remain largely unknown in plants. In this study, we identified a RanBP2-type zinc finger protein gene (SlRBZ) in tomato. SlRBZ was constitutively expressed in roots, stems, leaves, flowers and fruits. The SlRBZ-GFP fused protein was localized in the nucleus. Overexpression of SlRBZ resulted in chlorosis and dwarf phenotypes in tomato. Determination of physiological index showed that chlorophyll, carotenoid, and GAs contents were evidently decreased in transgenic plants. Furthermore, the qRT-PCR and RNA-Seq analyses demonstrated that the transcription of the genes involved in these biosynthesis pathways obviously decreased in SlRBZ-OE plants. In addition, ultrastructural observation by transmission electron microscopy indicated that plastids could not develop into mature chloroplasts with normal chloroplast membrane and thylakoid membrane system in SlRBZ-OE plants. The results suggest that overexpression of SlRBZ may impair the biosynthesis of chlorophyll, carotenoid, and gibberellin through blocking chloroplast development, resulting in chlorosis and dwarfism in tomato.